Silica-based nanomaterials as designer adsorbents to mitigate emerging organic contaminants from water matrices. (December 2020) - Zeb, Shakeel; Ali, Nisar; Ali, Zarshad; Bilal, Muhammad; Adalat, Bushra; Hussain, Sajjad; Gul, Saima; Ali, Farman; Ahmad, Rashid; khan, Sabir; Iqbal, Hafiz M.N.
Graphical abstract: Highlights: Herein, we reviewed the mitigation of organic pollutants using silica-based mesoporous materials. Silica-based mesoporous materials – A candidate adsorbent for organic wastes. Source and occurrence of organic pollutants in the environmental compartments are described. Abstract: The abatement of emerging organic contaminants from industrial effluents and wastewater is a key challenge for environmental scientists around the globe. Many industries release their effluents containing organic compounds into water bodies, which make them contaminated and hazardous for the living ecosystem. Controlling water pollution has become challenging in recent years. Adsorption technology has received worldwide acceptance for the removal of various classes of pollutants from water. Though many sorbents like activated carbons and other low-cost materials are used for the elimination of organic pollutants from water, their widespread use is restricted due to high costs and lower removal efficiency. In this context, silica and silica-based adsorbents have gained incredible attention due to their probable applications in the field of catalysis, separation, and green synthesis. This review describes various classes of silica with emphasis on mesoporous silica-based adsorbents and also comprehensively underline an up to date description, development, and their use for the removal of organic pollutants.